Effect of RAAS blockers on adverse clinical outcomes in high CVD risk subjects with atrial fibrillation: A meta-analysis and systematic review of randomized controlled trials. Issue 26 (June 2016) - Chaugai, Sandip; Sherpa, Lhamo Yanchang; Sepehry, Amir A.; Arima, Hisatomi; Wang, Dao Wen
Abstract : Abstract: Recent studies have demonstrated that atrial fibrillation significantly increases the risk of adverse clinical outcomes in high cardiovascular disease risk subjects. Application of renin–angiotensin–aldosterone system blockers for prevention of recurrence of atrial fibrillation and adverse clinical outcomes in subjects with atrial fibrillation is a theoretically appealing concept. However, results of clinical trials evaluating the effect of renin–angiotensin–aldosterone blockers on adverse clinical outcomes in high cardiovascular disease risk subjects with atrial fibrillation remain inconclusive. A pooled study of 6 randomized controlled trials assessing the efficacy of renin–angiotensin–aldosterone blockers on subjects with atrial fibrillation was performed. A total of 6 randomized controlled trials enrolled a total of 53, 510 patients followed for 1 to 5 years. RAAS blockade therapy was associated with 14% reduction in the incidence of heart failure (OR: 0.86, [95%CI: 0.76– 0.97], P =0.018) and 17% reduction in the incidence of CVE (OR: 0.83, [95%CI: 0.70–0.99], P = 0.038). The corresponding decline in absolute risk against heart failure (ARR: 1.4%, [95%CI: 0.2–2.6%], P = 0.018) and CVE (ARR: 3.5%, [95%CI: 0.0–6.9%], P = 0.045) in the AF group was much higher than the non-AF group for heart failure (ARR: 0.4%, [95%CI: 0.0–0.7%], P = 0.057) and CVE (ARR: 1.6%, [95%CI: –0.1% to 3.3%], P = 0.071). No significant effect was noted on all-cause or cardiovascular mortality, stroke, or myocardial infarction. This study suggests that RAAS blockade offers protection against heart failure and cardiovascular events in high cardiovascular disease risk subjects with atrial fibrillation.